2017
DOI: 10.5897/jat2016.0236
|View full text |Cite
|
Sign up to set email alerts
|

Taxation revenue and economic growth in Africa

Abstract: As most developing countries strive to achieve economic growth and development through taxation, they face numerous economic challenges. The debate on the effectiveness of taxes as a tool for promoting growth and development remains inconclusive, as several studies have indicated mixed impacts of tax on economic growth. Against this background, the study investigated the impact of taxation on economic growth in Africa from 2004 to 2013. The study carried out various preliminary tests including descriptive stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 13 publications
4
17
0
3
Order By: Relevance
“…They concluded that tax revenue significantly influences economic growth in Ghana. Onakoya et al (2017) analyzed the impact of tax revenue on economic growth in Africa. They used annual data from 2004 to 2013 for 16 African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that tax revenue significantly influences economic growth in Ghana. Onakoya et al (2017) analyzed the impact of tax revenue on economic growth in Africa. They used annual data from 2004 to 2013 for 16 African countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that the impact of tax on economic growth may depend on which direct or indirect tax contributing most to economic growth. There are limited researches and inconclusive results regarding the impact of direct and indirect tax on economic growth of African countries (Onakoya, Afintinni, & Ogundajo, 2017). Seeing this gap, this research seeks to examine the impact of direct and indirect tax on the Nigerian economic growth (with Nigeria being an African country).…”
Section: Introductionmentioning
confidence: 99%
“…The findings concluded the positive impact of tax structure on economic growth. (Onakoya et al, 2017) used ordinary least square, fixed effect and random effect model, the findings confirm the positive and significant coefficients for all the estimations [33]. (Ojong et al, 2016) preferred the random effect estimation, using the Nigerian economy, and confirmed the positive and significant relationship between tax and the economy [34].…”
Section: Econometric Estimations Used By Previous Studiesmentioning
confidence: 82%